THE USE OF MODERN TECHNOLOGIES IN TEACHING MATHEMATICS - Yuldoshev Mansur Najmiddin o'g'li (Euro Asian Journal Publishing, 2024)
In recent years, the integration of modern technology into education has transformed the way subjects are taught and learned, with mathematics being no exception. This evolution has not only made mathematics more accessible and engaging but also provided educators with new tools and methodologies to enhance learning outcomes. The use of technology in teaching mathematics has revolutionized traditional approaches, offering innovative ways to engage students, personalize learning, and improve understanding of complex concepts.
Keywords: modern technology; mathematics education; interactive learning